The Effect of Knowledge and Parenting on Stunting of Toddlers in Muna Barat, South East Sulawesi (Universitas Negeri Semarang, 2019)
Stunting is a nutritional problem that has lasted a long time in toddlers aged 6-59 months. Stunting is assessed based on the ratio of a child's height to the standard height of a child in a normal population according to age and gender. The purpose of this study was to analyze the direct and indirect influence of knowledge factors on stunting through parenting of toddlers. This research is a quantitative study using a case control study approach. A sample of 100 respondents consisting of 50 case samples and 50 control samples was obtained by taking techniques using fixed disease sampling. The data analysis using chi square test and multivariate analysis. The result of this study showed that the knowledge directly affects the stunting with values (b=1.25; CI 95%=0.27 to 2.23; p=0.012). The knowledge has an indirect but insignificant effects on stunting events through the mediation of parenting with values (b=0.21; CI 95%=-0.78 to 1.2; p=0.667). Parenting directly affects stunting with values (b=1.2; CI95%=0.13 to 2.26; p=0.027). The conclusion of this research was knowledge directly affects the stunting in Toddler. The results of this study are expected to be a reference material for related parties in improving nutrition problems (stunting), especially in increasing mothers’ knowledge and parenting.